A new Platystele (Orchidaceae, Pleurothallidinae) from the western mountains of Colombia - Reina Rodríguez, Guillermo Alberto (2018)
A new species of miniature orchid, Platystele riograndense, endemic to the Pacific slope of the western Cordillera, Munici- pality of Restrepo, Valle del Cauca, Colombia, is described and illustrated. Platystele riograndense is similar to P. filamento- sa, but the new species has wider leaves, denser and shorter inflorescences and sigmoid (versus convex) lip. Ecological notes are provided. It is the second new species described of Canyon of Rio Grande new protected area in the last four years.